Retraction note: Predictive value of machine learning models for lymph node metastasis in gastric cancer: A two-center study - Jia-Ping Yan; Jin-Lei Wang (World Journal of Gastrointestinal Surgery, 2025)
In this retraction note, we describe the World Journal of Gastrointestinal Surgery (WJGS ) Editorial Office’s decision and reason for retracting an article published in WJGS , volume 16, issue 1.